A constituição da subjetividade: Hegel e a ordem das sucessões cumulativas - Araújo, Vitor Vasconcelos de (2020)
This work tried to present the stages of formation of the idea of the Self. In the first chapter we approach the constitution of the Self through the point of view of the substance, whose resolution of internal contradictions to substantial thought provided us with the need for the Concept to determine itself under the condition that it produces an order of constancy. In the second chapter, we present the stages of the formation of the Self from the point of view of formal subjectivity, whose path led to the production of syllogistic forms. These forms provide the Self with not only the newly acquired stability through substantial thinking, but also logical circularity through the dissolution of syllogism as a subjective-formal process. The process of determining the Self would not be complete without first introducing teleology, or a way of building purposes that guide the production of the Concept. Teleology, warns Hegel, cannot be anything other than an immanent process. Due to the internality of the vectors responsible for establishing the procedural nature of Being, there is no external author capable of architecting the Concept. Hegel will also need to go through the opposition between subjective purposes and the objective world, a contradiction that offers a dead idea of objectivity, since as an immediacy, the objective world is only a reality given beforehand. Life, as the realization of an internal purpose, resolves the internal contradiction between subjectivity and objectivity and is an effectiveness that is exists in conformity with the Concept. At the end of the Hegelian exposition on the method, we will question the determined nature of Hegelian thought. For this, we will use E. Luft's diagnosis and will present the idea of a dialectic that is incompatible with itself. In addition to the form of ambivalence presented by E. Luft, between the positive speculation and the negative aspect of the critic, we find in the idea of Stufen another type of incompatibility. Stufen could be read as successive, determined and anticipatory processes. In that regard, they would be nothing more than an order of effectiveness that is a fulfillment of previous disposition of the Being. They could also be read as processes that carry within themselves all the negations of a cumulative path, whose presentification would exist in the condition of position of new logical processes.